Development of entrepreneurship in the oil industry of the Stavropol Krai: problems and prospects - N. E. Dimurina; V. V. Roshchupkina (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. The article examines the state of the oil industry of the Stavropol Krai, the problems of the development of the oil refining sector, which results in the purchase of petroleum products at higher prices compared to regions that have their own refining capacities, which negatively affects the economic efficiency of the region. The analysis of the development of entrepreneurship in the oil industry, the key enterprise of which is LLC «Stavropolneftegaz», as the main operator of the oil fields of the region, allowed us to identify problems and priority areas of activity to increase the investment attractiveness of the oil industry in the region.Materials and methods. The analysis of scientific and methodological literature on the subject under consideration, comparison, systematization,  generalization, research of relevant documentation were used in the work.Results and discussion. The oil industry of the region does not occupy a leading position affecting the efficiency of the development of the regional economy, and its share in the regional budget is 9,2 % of all tax revenues, but, nevertheless, oil and petroleum products occupy a large niche in the balance of energy resources of the region. These facts confirm that the regional fuel and energy complex is a successful, steadily growing industry. The government of the region is aimed at stabilizing oil production, contributing to the implementation of several major projects.Conclusion. The prospects for the development of crude oil production are the identification of oil deposits in unconventional objects of the Meso-Cenozoic cover traps with complex shielding and in carbonate reef structures; the study of oil and gas potential of deeplying complexes of the Paleozoic basement, which implies significant costs for thickening the network of regional seismic profiles and drilling parametric wells; involvement in the exploitation of previously studied small deposits of hydrocarbon raw materials.